2019
DOI: 10.3390/app9030522
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Intra-Annual Patterns of Sedimentary Evolution in Tidal Flats Impacted by Laver Cultivation along the Central Jiangsu Coast, China

Abstract: Human activities such as the rapid development of marine aquaculture in the central Jiangsu coast have had a marked impact on the tidal flat morphology. This research focuses on characterizing the spatial expansion of laver cultivation and its influence on the sedimentary evolution of tidal flats in the central Jiangsu coast. First, seasonal digital elevation models (DEMs) were established using 160 satellite images with medium resolution. Then, laver aquaculture regions were extracted from 50 time-series sate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…the alongshore reclamation engineering areas and its influence degree is reduced with the increase of the offshore distance, most of affected area decreases on account of resistance effect of structures, few bank angle area increases on account of the shrink of water crossing. It also can be found that the scope of influence of velocity in the period of the flood tide is larger, which is in accordance with the fact of flood tide prevailing [12]. After the construction of the polder project, an artificial headland was formed in the original open water, so the tidal exchange of this sea area is inevitably affected.…”
Section: Anthropogenic Influences On the Hydrodynamicsupporting
confidence: 54%
“…the alongshore reclamation engineering areas and its influence degree is reduced with the increase of the offshore distance, most of affected area decreases on account of resistance effect of structures, few bank angle area increases on account of the shrink of water crossing. It also can be found that the scope of influence of velocity in the period of the flood tide is larger, which is in accordance with the fact of flood tide prevailing [12]. After the construction of the polder project, an artificial headland was formed in the original open water, so the tidal exchange of this sea area is inevitably affected.…”
Section: Anthropogenic Influences On the Hydrodynamicsupporting
confidence: 54%
“…The temporal change in tidal flats depends on local conditions, such as coastal morphology, sediment, hydrodynamics, and human activities (X. Chen et al, 2020;Lu et al, 2019;Jeong et al, 2019 ). In addition, the elevation range of the satellite derived tidal flat topography can be smaller than that from airborne lidar data (Figure 4), which may be explained by the fact that the 10-m resolution Sentinel-2 imagery is unable to characterize some narrow tidal creeks with lower elevations.…”
Section: Discussionmentioning
confidence: 99%
“…In Figures 4f and 4g, a general consistency and some tiny differences between tidal creeks derived from our results and airborne lidar data can be observed, which may be caused by different acquisition dates of satellite data and airborne lidar data. The temporal change in tidal flats depends on local conditions, such as coastal morphology, sediment, hydrodynamics, and human activities (X. Chen et al., 2020; Lu et al., 2019; Jeong et al., 2019 ). In addition, the elevation range of the satellite derived tidal flat topography can be smaller than that from airborne lidar data (Figure 4), which may be explained by the fact that the 10‐m resolution Sentinel‐2 imagery is unable to characterize some narrow tidal creeks with lower elevations.…”
Section: Discussionmentioning
confidence: 99%
“…However, these approaches are restricted by the large scale of observation required, and by the difficulty in simulating tidal creek characteristics under complex natural conditions. Remote sensing has major advantages for tidal flat observation [31][32][33][34], and light detection and ranging (LiDAR), in particular, can generate three-dimensional terrain data, and has been widely applied in intertidal zones [35][36][37]. Previous efforts using remote sensing have focused mainly on the extraction of tidal creeks [4,16,38,39], the analysis of morphological characteristics [40,41], and the process of evolution of tidal creeks [21,29,42,43].…”
mentioning
confidence: 99%